Effects of age of cow at first calving, period of calving and calving sequence on calving interval of N'dama and Keteku Cattle and their crosses in Southwestern Nigeria. - AKINOKUN, O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Calving records of N'dama and Keteku cows on range in the humid tropical environment of southwestern Nigeria were analysed to determine the effects of cow age at first calving, period of calving and calving sequence on length of calving intervals. Cow age at first calving and calving sequence significantly affected calving intervals (P<.01). Heifers calving for the first time at 3.6 - 4 years had an average calving interval of 511 days while heifers calving for the first time before 3.6 years had intervals that were 36 days longer. Those calving for the first time at over four years had average calving intervals that were shorter by 73 days. There was a progressive decrease in length of calving interval as calving sequence increased. Period of calving had no significant effect on length of calving interval.